2018
DOI: 10.1038/s41598-018-34534-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure of bacterial oligosaccharyltransferase PglB bound to a reactive LLO and an inhibitory peptide

Abstract: Oligosaccharyltransferase (OST) is a key enzyme of the N-glycosylation pathway, where it catalyzes the transfer of a glycan from a lipid-linked oligosaccharide (LLO) to an acceptor asparagine within the conserved sequon N-X-T/S. A previous structure of a ternary complex of bacterial single subunit OST, PglB, bound to a non-hydrolyzable LLO analog and a wild type acceptor peptide showed how both substrates bind and how an external loop (EL5) of the enzyme provided specific substrate-binding contacts. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…Similarly, bacterial OSTs, such as Campylobacter jejuni PglB ( Cj PglB), are generally composed of a single subunit which is homologous to the STT3 catalytic domain of eukaryotic OSTs. 108 There is a strong topological resemblance between bacterial and eukaryotic OST-dependent glycosylation as they both involve the cytoplasmic construction of an LLO that is flipped into an oxidative compartment (the periplasm in bacteria and the endoplasmic reticulum (ER) in eukaryotes) before being transferred to an acceptor sequon. 75 The colocalization of both the LLO and the OST in the membrane means that polypeptide modification is only dependent on 2D diffusion and enables cotranslational modification in eukaryotic systems.…”
Section: The “Parts” Of Synthetic Glycobiology: An Engineer’s Guide Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, bacterial OSTs, such as Campylobacter jejuni PglB ( Cj PglB), are generally composed of a single subunit which is homologous to the STT3 catalytic domain of eukaryotic OSTs. 108 There is a strong topological resemblance between bacterial and eukaryotic OST-dependent glycosylation as they both involve the cytoplasmic construction of an LLO that is flipped into an oxidative compartment (the periplasm in bacteria and the endoplasmic reticulum (ER) in eukaryotes) before being transferred to an acceptor sequon. 75 The colocalization of both the LLO and the OST in the membrane means that polypeptide modification is only dependent on 2D diffusion and enables cotranslational modification in eukaryotic systems.…”
Section: The “Parts” Of Synthetic Glycobiology: An Engineer’s Guide Tmentioning
confidence: 99%
“… 117 Finally, bacterial OSTs possess unique specificities for acceptor sequons and LLOs compared to eukaryotic OSTs. 108 , 118 Acceptor sequons for bacterial N -linked OSTs do resemble the eukaryotic N-X-S/T motif; however, some bacterial OSTs additionally require a negatively charged residue (D/E) at the X –2 position relative to the glycosylated asparagine. 59 , 85 87 For example, an optimized acceptor sequence, D-Q-N-A-T, has been identified for Cj PglB 81 and has been implemented as a GlycTag to direct glycosylation to flexible regions of proteins of interest.…”
Section: The “Parts” Of Synthetic Glycobiology: An Engineer’s Guide Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structures of the eubacterial OST Compylobactor lari, PglB, in the presence of acceptor peptides (D/EXNXT/S) have greatly enhanced the understanding of the mechanism of N-linked glycosylation [33,35]. Furthermore, a crystal structure of the apo form of AglB from the archaeon Archaeoglobus fulgidus has shown that despite low sequence similarity, archaea use a structurally and likely functionally similar mechanism for oligosaccharide transfer [39].…”
Section: Bacteria and Archaeamentioning
confidence: 99%
“…The majority of the biosynthetic processes that produce glycoproteins can broadly be divided into two categories, i.e. enzymes involved in N-glycosylation that transfer a pre-assembled lipid-linked glycan en bloc to an asparagine residue in the consensus sequence N-X-(S/T) (where X ≠ Pro), such as the well-known eukaryotic OST complex 5 and its bacterial homologue PglB, 6 and enzymes responsible for O-linked glycosylation, that transfer single carbohydrate residues from soluble nucleotide-activated substrates to serine and threonine, such as O-GlcNAc transferase (OGT) 7 and O-GalNAc transferases involved in the initiation of mucin glycosylation. 3 N-linked glycosylation occurs predominantly cotranslationally on a limited number of residues, and subsequent trimming and/or further modification of the glycan results in a tremendous diversity in glycoforms, as exemplified by the >200 erythropoietin glycoforms identified in a single sample.…”
Section: Introductionmentioning
confidence: 99%